New Method for Enhancement of Histo-Pathological Diagnosis of Prostate Cancer - Kochiashvili, MD PhD, Ciorgi; Khuskivadze,MD PhD, Alexandre; Partsvania, PhD, Besarion; Chubinidze, Ketevan; Sulaberidze, Tamaz (Journal of Medical Biomedical and Applied Sciences, 2018)
In general, histomorphologic examination of a prostate tissue is necessary after the prostatectomy.This study was carried out to investigate a possibility of the usage of polarized light for enhancement of histo-pathological diagnosis of prostate cancer. Experiments were carried out in isolated prostates. For the obtaining of prostate infrared images a light source in the spectral range of 840-900 nm was used. Infrared light polarization measurement was perform edusing polarizers working in 700-2000 nm. Infrared polarized light incident on a CCD camera matrix was converted into electrical signals and sent to the PC for the creating visible image. Specially elaborated software converts the electrical signals, received from the CCD camera, from near infrared (NIR) into visible image, that allows us to discriminateinfrared images of healthy tissue from the malignant ones. It is shown that the intensity of near infrared (NIR) light passing through the cancerous outgrowth is lower than the intensity of NIR light passing through the non-cancerous tissue and the cancerous formations are differentiated as the dark areas in the relatively white background. It has been shown that the utilization of polarized NIR light for prostate cancer targeting and visualization is a promising imaging modality for the discrimination of malignant areas in prostatectomy specimens.